The Personalities Analysis of “Jackson Maine And Ally” on “Star Is Born” Movie 2018 - Tri Rudy Puji Setyawan; Richayatul Janah (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2022)
The purpose of this study is to describe the positive personality values and negative personality values of the main character in “a Star is Born Movie 2018”. In literary works, there are many things that can be done to be studied, but researcher only focused on the personalities of the two main players. The purpose of this research is to make it easier for readers to recognize the personality. This research is presented based on a literature review from experts, related to this research contains several topics that are used to support the analysis in this study. The literature review is used to strengthen the results of the study, several related keywords in the research of this film serve to facilitate the reader understands the important parts that will be explained in this study. The researcher has also compared this research with other studies related to personality research from a film. The method of this study is descriptive analytical method. Data and data sources are from the scenes and dialogues in this film which are collected by using documenting technique. The results of the study from this film are; Jackson's negative personality can be improved with the support, affection and hard work of Ally. The positive impact of both is that Jackson is trying to become a better person and Ally's career in music is increasing. from this film, we can get moral values that we can apply to families, students or people around us to instill a positive attitude and thinking in behaving and supporting each other and instilling love for others. Keywords: Personalities, A Star is Born Movie 2018, Literature Study